Contraction intensity and velocity on vastus lateralis sEMG power spectrum and amplitude - Miller, J.; Croce, R.; Smith, W.; Horvat, M. (Perceptual and Motor Skills, 2012)
Effect of contraction intensity [100%, 75%, 50%, and 25% maximum voluntary contraction (MVC)] and movement velocity [0° (isometric)], 50°, 100°, 200°, and 400°/sec. [isovelocities]) on root mean square amplitude (SEMG--RMS) and median frequency power spectrum (SEMG-MNF) of vastus lateralis (VL) surface electromyography was investigated with ten healthy female university students. Peak torque (PT), mean torque (MT), SEMG--MNF, and SEMG--RMS, analyzed using separate repeated-measures analyses of variance (p < .05), indicated: (1) an inverse relation between PT and MT and movement velocity, (2) greater SEMG--MNF values during all isovelocity conditions compared with isometric conditions, with highest values occurring at 50°/sec. and at 100% and 75% MVC, and (3) at all contraction intensities SEMG--RMS values were higher during dynamic movements than isometric movements and highest at 200°/sec. Isovelocity contractions were inferred to facilitate a greater recruitment of fast-twitch fibers (via increased SEMG--MNF), which was intensified at 50°/sec., whereas greater overall muscle activation was found at 200°/sec.